A new gluten‐free product: Brown rice bulgur, and its physical and chemical properties. Issue 3 (16th January 2021) - Candal‐Uslu, Cihadiye; Mutlu, Ceren; Koç, Andaç; Bilgin, Duygu Gizem; Erbaş, Mustafa
Abstract: In this research, a new alternative food product, defined as brown rice bulgur (BRB), rich in functional components compared to white rice and cooked in a short time compared to brown rice was developed for society especially individuals with gluten intolerance and celiac disease. BRB was produced with two different methods as boiling (BRB‐B) and steaming (BRB‐S). The cooking time of raw brown rice decreased from 30 to 9 min in BRB samples. The phytic acid content of BRB samples decreased by about 15% and enzyme resistant starch content of BRB‐B and BRB‐S samples increased by about 9% and 21% compared to brown rice, respectively. The produced BRB samples were in the medium GI food group. In conclusion, it was evaluated that the newly developed BRB is superior than brown rice, white rice, and wheat bulgur in terms of short cooking time, lower GI, and being gluten‐free, respectively. Practical applications: In this study, brown rice bulgur has been produced from brown rice, unpreferable by consumers due to its long cooking time, hard texture, and dark color, with wheat bulgur production method. This new food product includes the advantages of wheat bulgur such as resistivity to insect and mold activity because of applied high‐temperature thermal process and drying process, but do not include the disadvantages of brown rice such as long cooking time. Additionally, it could be attention to some consumers because of being a new gluten‐free product. The obtained data can help diversify this product in the food industry.